2007
DOI: 10.1158/1535-7163.mct-06-0641
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to c-KIT kinase inhibitors conferred by V654A mutation

Abstract: Certain mutations within c-KIT cause constitutive activation of the receptor and have been associated with several human malignancies. These include gastrointestinal stromal tumors (GIST), mastocytosis, acute myelogenous leukemia, and germ cell tumors. The kinase inhibitor imatinib potently inhibits c-KIT and is approved for treatment of GIST. However, secondary point mutations can develop within the kinase domain to confer resistance to imatinib and cause drug-resistant relapse. A common mutation, which resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 49 publications
1
46
1
Order By: Relevance
“…Such differences are often observed with inhibitors of protein kinases (e.g., see refs. 28,29) and may have multiple causes. First, nonlinearities in the Western blots may have caused the IC 50 for tyrosine phosphorylation to appear at a higher concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are often observed with inhibitors of protein kinases (e.g., see refs. 28,29) and may have multiple causes. First, nonlinearities in the Western blots may have caused the IC 50 for tyrosine phosphorylation to appear at a higher concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of imatinib resistance varies between the different sites of secondary kinase mutations. On the basis of a number of in vitro studies, secondary mutations involving the ATP binding pocket were found to directly inhibit imatinib binding, especially the T670I "gatekeeper" mutation (46,49,50). This mutation is homologous to the resistance mutations of the "gatekeeper" threonine residues in BCR-ABL (T315I) and epidermal growth factor receptor (EGFR; T790M; refs.…”
Section: Imatinib Resistancementioning
confidence: 99%
“…However, because acquired resistance is often observed in GIST and other cancers treated with TKIs or other targeted therapies, further rationally developed therapies against oncogenic KIT are necessary (12)(13)(14)(15)(16)(17). Moreover, it is not clear why anti-KIT mAbs that are ∼1,000-fold more potent than the TKI imatinib and 100-fold more potent than the TKI sunitinib in blocking the tyrosine kinase activity of WT KIT fail to block the activity of the oncogenic V560D KIT mutant.…”
mentioning
confidence: 99%